Dengue Virus Induced COX-2 Signaling Is Regulated Through Nutrient Sensor GCN2 - Afroz, Sumbul; Battu, Srikanth; Giddaluru, Jeevan; Khan, Nooruddin (Frontiers in Immunology, 2020)
Nutrient sensor GCN2 plays crucial role in the maintenance of cellular homeostasis during the condition of amino acid deprivation. Dysfunction in the GCN2 signaling underlies several chronic metabolic diseases. Recent studies highlight the anti-viral potential of GCN2 against RNA viruses such as Sindbis and HIV. However, its effect on dengue virus (DENV) pathogenesis remains poorly understood. Herein, we report that GCN2 deficient cells show increased DENV replication and viral yield in the culture supernatants compared to WT cells infected with DENV. Notably, enhanced DENV replication in GCN2-/- cells is associated with increased COX-2/PGE2 signalling. Conversely, GCN2 overexpression/activation effectively contains DENV infection by inhibiting COX-2/PGE2 signalling. Mechanistically, deletion of GCN2 triggers enhanced production of COX-2/PGE2 through profound activation of Iκκ-NF-κB signalling pathway. Altogether our results unveil a hitherto unrecognized role of GCN2 in DENV pathogenesis, thereby suggesting that targeting GCN2 pathway might offer a novel therapeutic intervention against DENV infection.